South-Asian niche as the poetic helicon of Taufiq Rafat: a metapoetic study (Acta Scientiarum. Language and Culture, 2022)
The genre of metapoetry thematizes the fictional elements – the inspiration of a poet, his poetic process, meta-poetic metaphors, the role of the poet in society, and intertextual references – partaking in the making of poetry explicitly or implicitly carried through a poem within a poem technique. This paper presents Eva MÃ¼ller-Zettlemann’s theoretical pronunciation of meta-poetic elements, i. e., poetic inspiration, poetic process, and meta-poetic metaphors, at play in the metalyrics of Taufiq Rafat from his anthologies Arrival of the Monsoon: Collected Poems 1947-78 (1985) and Half Moon: Poems 1979-1983 (2008). Rafat’s inspiration is the South-Asian terra firma and lived experience that makes him infuse the regional sensibility through a poetic process of perceiving and penning down immediately. His meta-poetic metaphor involves the invention of an image of cultural genesis that informs the process of poetic creativity. Moreover, the study also considers the explicit expression of the role of the poet in society and the functions of poetry in Rafat’s poems, otherwise a prose phenomenon. Thus, the paper analyzes the conscious expression of the construction of South-Asian singularity inspired by the cultural kernel in content and form in Rafat’s metalyrics.